Employee Performance: The Effect of Work Motivation, Work Discipline, and Job Satisfaction at one of music companies in Indonesia - Damar Aji Irawan; Hanita Marsherina; Jessica Evasari; Marceline (Kusuma Negara Business School, 2020)
This research aims to investigate the variables that influence employee performance in PT XYZ Indonesia. This study is an associative quantitative research. The data were collected using questionnaires. The population of this research was 33 employees of PT XYZ in Jakarta, Indonesia. To select the sample size, census methodology was used. The respondents are active employee of PT XYZ. The data was analyzed using multiple linear regression analysis using SPSS software. The result showed that work motivation, work discipline, and job satisfaction simultaneously have significant effects on employee performance. While partially work motivation and job satisfaction do not have significant effects on employee performance and work discipline partially has significant effect on employee performance.